The Influence of Guidance and Counseling Teacher's Role, Emotional Maturity, and Self-Control on Aggression Behavior of High School Students - Ali Nasith (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to examine the influence of the role of school counselors (Bimbingan dan Konseling/BK), emotional maturity, and self-control on aggressive behavior among high school students. Employing a quantitative explanatory approach and utilizing Structural Equation Modeling based on Partial Least Squares (SEM-PLS), the research involved high school students selected through purposive sampling techniques. The findings reveal that all three independent variables, namely, the role of school counselors, emotional maturity, and self-control have a significant negative effect on students' aggressive behavior. This indicates that the more effective the counselor’s role, the higher the students' emotional maturity, and the better their self-control, the lower the tendency to exhibit aggressive behavior. Therefore, it can be concluded that the active role of school counselors, along with the reinforcement of students’ psychological aspects: particularly emotional maturity and self-regulation plays a crucial role as both a preventive and curative strategy in reducing aggressive behavior in the school environment.